Voluntary Exercise Improves Cardiac Function and Prevents Cardiac Remodeling in a Mouse Model of Dilated Cardiomyopathy - Deloux, Robin; Vitiello, Damien; Mougenot, Nathalie; Noirez, Philippe; Li, Zhenlin; Mericskay, Mathias; Ferry, Arnaud; Agbulut, Onnik (Frontiers in Physiology, 2017)
Objective: Despite the indubitable beneficial impact of exercise on the prevention of cardiovascular diseases, few studies have been made to clarify the effects of exercise training in non-ischemic cardiomyopathies. Here, we investigated the impact of voluntary chronic exercise training on cardiac function in a murine model of non-ischemic dilated cardiomyopathy (αMHC-MerCreMer:Sf/Sf), induced by cardiac-specific and tamoxifen-inducible inactivation of the Serum Response Factor. Materials and Methods: Seven days after tamoxifen injection, twenty αMHC-MerCreMer:Sf/Sf mice were allocated to sedentary (n=8) and exercise (n=12) groups. Seven αMHC-MerCreMer:Sf/Sf mice without tamoxifen treatment were used as control (sedentary). Exercise group underwent 4 weeks of voluntary running on wheel (1.8±0.12 km/day). Cardiac function, myocardial fibrosis and mitochondrial energetic pathways were then blindly assessed. Results: Exercised mice exhibited less decrease of left ventricular (LV) fractional shortening and ejection fraction compared to sedentary mice. This correlated with a lesser degree of LV remodeling in exercised mice, as shown by a lower LV systolic intrerventricular septal and posterior wall thickness decrease from baseline values compared to sedentary mice. Moreover, exercised mice displayed a reduced genes expression of the stress-induced atrial and brain natriuretic factors. These protective effects were accompanied by a reduction of myocardial fibrosis. In addition, exercised mice exhibited a higher mitochondrial aconitase, voltage-dependent anion-selective channel 1 and PPAR gamma coactivators-1 alpha proteins levels suggesting that enhancement of mitochondrial biogenesis and/or metabolism slow down the progression of dilated cardiomyopathy in exercised animals. Conclusions: In conclusion, our results strongly support the role of voluntary exercise to improve outcomes in non-ischemic heart failure and also support its potential for a routine clinical use in the future.